ANALISIS YURIDIS PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL (Studi Kasus tentang PHK Di Dinas Tenaga Kerja Provinsi Sumatera Utara) - Nanci Yosepin Simbolon; Mhd Iqbal Sinaga; Betty Berliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
In the era of industrialization, the problems of industrial relations disputes are increasing and complex, so that mechanisms and institutions for resolving industrial relations disputes are needed that are fast, precise, fair, inexpensive, so that they can be resolved by upholding legal authority, legal certainty and justice. By using a normative juridical research method, collecting laws and regulations, namely Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes and the Manpower Act. The result of the discussion is that layoffs can occur because the company merges, consolidates, takes over, or separates the company and the employee is not willing to continue the working relationship or the entrepreneur is not willing to accept the worker or laborer. Another reason is the company's efficiency, the company closed because of continuous losses for two years, the company closed due to forced circumstances, and others.